Research progress on guided tissue regeneration membrane - YUAN Shuai; WANG Zuolin (Kouqiang hemian waike zazhi)
Periodontitis often leads to irreversible damage, and guided tissue regeneration (GTR) remains the primary therapeutic strategy for reconstructing lost hard tissue and periodontal attachment. However, current GTR membranes still face multiple limitations in complex clinical applications, highlighting the urgent need for the development of advanced GTR membranes with improved performance. This review systematically summarizes recent progress in GTR membranes from four key aspects, aiming to provide insights and perspectives for the future improvement and innovation of GTR membrane design.